Sequência didática sobre o movimento ondulatório com foco nas atividades experimentais - Souza, Walance Augusto da Silva (2021)
In this dissertation, held at pole 9 (nine) of the National Professional Master's Degree on the Teaching of Physics, at the Semi-Arid Federal Rural University, we present a proposal for a didactic sequence on the wave movement in which we privilege the use of experimental activities as a facilitating resource for a potentially meaningful learning. It was designed with the aim of bringing to the classroom learning situations, which are easy for students to perform under the guidance of the teacher. In the conception of the proposal we took into consideration the approaches of meaningful learning, of Ausubel, and the socio-interactionist theory, of Vygotsky and collaborators, which implied, from the methodological point of view, taking as a starting point in the planning and implementing of the activities the socio-cultural context of the students and their previous knowledge. The didactic sequence, constituted of 6 meetings with two classes of 50 minutes each, was applied in the modality of remote teaching in three groups of high school level at Claudio Martins full-time high school, located in Fortaleza, Ceará. The results of the evaluation, based on the presentation of the experimental activities by the students and in the application of a questionnaire with contents on wave movement contemplated in the didactic sequence show that the aims of the intervention proposal, despite the fact that it has been performed through synchronous classes, were satisfactorily achieved